PERIPHERAL RETINAL DRUSEN–LIKE DEPOSITS IN GUCY2C CONGENITAL SECRETORY DIARRHEA SYNDROME. Issue Volume 15:Issues 1(2021) (2021) - Cugley, Dean; Brislane, Nicholas; Guymer, Robyn; Carden, Susan
Abstract : Purpose: To report the presence of drusen in infancy, in a patient with Type 1 retinopathy of prematurity and a rare congenital sodium diarrhea secondary to a sporadic GUCY2C mutation. Methods: A case report generated by review of clinical course, with imaging of 1 patient and literature review. Results: A 1.075-kg infant born at gestation age 27 weeks was admitted to our institution with respiratory distress and secretory diarrhea. During screening for retinopathy of prematurity, peripheral drusen–like subretinal deposits were identified. There were no similar findings in either parent or family history of ocular pathologies. Their distribution is atypical for that seen in other causes of early onset drusen such as autosomal dominant drusen or Sorsby fundus dystrophy. Retinopathy of prematurity was identified, which progressed to Type 1, and was treated with bilateral indirect peripheral retinal photocoagulation at gestational age of 40 weeks. Fluorescein angiography was performed and was consistent with peripheral drusen. Optical coherence tomography of the central macula and an awake electroretinogram at 6 months were normal. Serial examinations confirmed no progression in the drusen-like deposits or in retinopathy of prematurity, with clinically appropriate visual development observed during close follow-up. Conclusion: We identify a unique ocular phenotype of retinal drusen–like deposits in an infant with a rare, sporadic GUCY2C mutation. Abstract : We report a case of infantile peripheral drusen–like deposits associated with congenital sodium diarrhea syndrome secondary to a sporadic GUCY2C mutation. Drusen have not been reported at this age, nor in association with this syndrome, and we hypothesize there may be a relationship between this ocular phenotype and genetic mutation.